Peran Disiplin Kerja Dan Budaya Organisasi Dalam Meningkatkan Kinerja Pegawai Pada Kantor Pemko Medan - Fadli Adnin Nasution; Aswin Pratama Harahap; Mirwansyah Putra Ritonga (Magister Manajemen Universitas Muhammadiyah Sumatera Utara, 2026)
This study aims to analyze the effect of work discipline and organizational culture on employee performance at the Personnel and Human Resource Development Agency of Medan City Government. Problem identification in this study includes lack of time management, lateness in work, and organizational culture that has not been fully implemented. The research method used is quantitative with an associative approach, where data is collected through questionnaires distributed to 60 employees. The results of the study indicate that work discipline has a significant effect on employee performance with a path coefficient value of 0.530 and P-Values of 0.000. In addition, organizational culture also has a significant effect on employee performance with a path coefficient of 0.355 and P-Values of 0.000. Simultaneously, these two variables have a significant effect on employee performance, with an F-value of 24.295 and P-Values of 0.000. This study concludes that increasing work discipline and organizational culture can contribute to improving employee performance.